Empowerment of PKK Mothers in Managing Household Waste to Become Eco Enzym to Maintain Environmental Cleanliness in Apuan Village, Susut District, Bangli Regency - I Wayan Suanda; I Gusti Ayu Rai; I Nengah Suka Widana; Dewa Made Alit; Ni Made Milati (Jurnal Pengabdian Masyarakat Bestari, 2023)
Apuan Village, Susut District, Bangli Regency has a wide expanse of green with the dominant livelihoods of the population as farmers, the tourism sector, laborers, civil servants, self-employed and other activities. In the activities of daily life of society can not be separated from the waste in the form of waste generated. Most of the organic waste from fruit skins and vegetable waste is disposed of in the TPA and the rest is placed in residential areas. Piles of garbage give an unfavorable impression and are less comfortable for tourism behavior. This condition also causes a foul odor, disrupts health and environmental cleanliness is very lacking. Management of household waste into products that have added value through the fermentation process as a form of empowering the PKK in Apuan Village. Managing household waste into eco enzymes provides multipurpose benefits including organic fertilizer for plants and environmental sustainability.